Indoor mapping technology study for smart cities - Gupta, Tanishq (2017)
With the advancement in the technology, objects can be represented effectively in their 3D digital models which accurately represents their physical counterparts. Navigation services and mapping based on geographical data have become very popular in supporting our everyday lives. Much of these services are currently available mostly for outdoor purposes, however applications for indoor purposes are being explored where most of the human activities take place which can help develop “Smart Cities”. The aim of this study is to develop an indoor mapping system for data collection in a building environment by exploring new, efficient and cost effective scanning devices. The conventional devices currently in use are expensive which makes them difficult to implement for large scale applications. The data will be collected using a 3D scanning camera technology which develops depth maps of various locations. Xbox Kinect Sensor and Stereolab’s ZED camera are being used and compared in this study. In addition, various 2D images of the location could be used to generate 3D digital model. Results on point cloud processing, RGB-D segmentation and recognition are presented. Comparisons between different scanning devices techniques are made based on resolution, lighting, accuracy, speed and memory. The study shows the possibility of using this technology in a large scale building environment in an autonomous method for the future. This technology can then be potentially used for commercial purposes especially to track progress in construction sites, for real estate, facility management, retail and augmented reality applications.